Glamour among value: P/E ratios and value investor attention. Issue 3 (1st August 2019) - Moore, Jordan
Abstract: The trailing‐four‐quarter price–earnings (P/E) ratio is the most popular fundamental value proxy. This article is the first to examine the P/E ratio as the preeminent measure of value investor attention. Trailing‐four‐quarter P/E ratios predict significantly greater cross‐sectional variation in stock returns than lagged P/E ratios or current price‐to‐book (P/B) ratios. P/E strategy returns are robust to variables that proxy for fundamental risk, variables mechanically related to P/E ratios, relative trading volume, and liquidity. The role of attention is evident in return patterns across long and short portfolios, day of the week, and time since formation. Stocks with low P/E ratios exhibit an increase in total trading volume driven by small trades, an improvement in liquidity, and lower idiosyncratic volatility. These patterns are consistent with the typical trading activity of individual investors, who have the strongest attention constraints.